Estudo randomizado sobre o alívio sintomático da aplicação de parafina na osteoartrite de mãos - Azevedo, Francisco Vileimar Andrade de (2023)
Currently, effective and safe therapeutic options for symptomatic control of hand osteoarthritis (OA) remain limited. This prospective, randomized, single-blind study investigates the efficacy of a paraffin bath (PB) in pain relief for patients with hand OA. A total of 75 patients diagnosed with hand OA were randomized into a PB therapy group or a control group. After 4 weeks, PB therapy showed a mean reduction of -1.6 in pain as measured by the visual analogue scale (VAS), with significant improvements in manual functionality and no adverse events reported. The study concludes that PB therapy provides early and clinically significant pain relief, making it a viable non-pharmacological management option for hand OA.